Research of Non-steady Working Condition Transmission Ratio Control of New Type Mechanical CVT - Liang Chujun (Jixie chuandong)
In order to solve the problem of the poor dynamic response characteristics of new type mechanical CVT under non- steady working condition,a new type mechanical CVT is regarded as the research object,the principle and the working state of CVT are analyzed to obtain CVT transmission ratio variation under non-steady working condition,and the CVT fuzzy PID transmission ratio control system is established,finally,the new- type mechanical CVT non- steady PID control system feasibility is validated. The results show that non-steady state transmission ratio controls CVT output torque and transmission ratio in the non- steady state transmission control can guarantee a smaller overshoot and within a relatively short time reach a stable value.